Islam and Civilization (Analysis Study on The History of Civilization in Islam) - Islam , Muhammad Hifdil (LPPPM STAI Darul Hikmah Bangkalan, 2019)
The history of Islamic civilization is one of the most important fields of study of Islamic studies. Islamic history is events or events that really happened in the past that are entirely related to the religion of Islam. Islam is too broad in scope, so Islamic history has become a broad scope. Among them are related to the history of the process of growth, development, and the spread of Islam, figures who develop and spread Islam, the history of progress and setbacks achieved by Muslims in various fields, such as in the fields of religious and general science, culture, architecture politics, government, war, education, economy, and so on. The History of Islamic Civilization is a product description of the activities of the life of the Islamic ummah in the past that originated in Islamic values. This article will explores the history of civilization in Islam and How the civilization of Islam is developed.